The anova to mixed model transition. (September 2016) - Boisgontier, Matthieu P.; Cheval, Boris
Abstract: A transition towards mixed models is underway in science. This transition started up because the requirements for using analyses of variances are often not met and mixed models clearly provide a better framework. Neuroscientists have been slower than others in changing their statistical habits and are now urged to act.